Self-worth and its relationship to motivation to work from the Public secondary school teachers’ point of view in Irbid Governorate in Jordan - Barakat, Abeer Abdul-Hafiz; Al-Ajili, Shatha Abdul-Baqi (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the self-worth and its relationship to motivation to work from the public secondary school teachers’ point of view in Irbid governorate in Jordan. Descriptive relational approach was used. Two scales were used, namely: the self-worth scale and the motivation towards work scale. The two scales were applied to a stratified random sample of (352) male and female teachers in public secondary schools in Irbid governorate, of the first semester (2019-2020). The results showed that the level of self-worth among public secondary school teachers in the governorate of Irbid obtained an overall average (3.98 out of 5), as a rating (high). Furthermore, the level of motivation towards work obtained an overall average (3.72 out of 5), as a rating (high), and at the level of the fields the reasons for motivation related to the teacher got the highest average (3.76), followed by the reasons related to the work environment with an average (3.71) and finally the reasons for society with an average (3.69), all of them with a (high) rating. The results also showed a positive correlation between self-worth and motivation to work among public secondary school teachers in Irbid governorate, which reached (0.62), which is a (medium) relationship and based on the results, a set of recommendations have been proposed, including the need to develop new and innovative mechanisms and methods that work to raise the self-worth of teachers, in a way that improves their performance and increases their motivation towards work.